Boundary Layer Solutions For Convective Flow Via Various Group Transformation Methods - Uddin, Mohammed Jashim (2013)
In this thesis, two-dimensional laminar convective external boundary layer flow with heat/mass transfer under various physical configurations and in the presence of magnetic field, chemical reaction, radiation, viscous dissipation, heat source or sink, dispersion, melting, thermophoresis, Brownian motion and Joule heating have been investigated. Velocity slip or no slip boundary conditions, the thermal convective or thermal slip boundary conditions have been taken into consideration. The fluid is assumed to be Newtonian (regular and nano), viscous, incompressible, hydrodynamic or magnetohydrodynamic and has constant or variable physical properties. Both steady and unsteady boundary layers have been taken into account. A thorough presentation of the applications of various transformation group (one parameter and two parameters) to the problem of boundary layer equations is given. New as as well as existing group invariant transformations are developed to transform the transport equations to similarity equations. The similarity equations have been solved numerically by the Runge-Kutta-Fehlberg fourth-fifth order numerical method for various values of the controlling parameters. Graphs have been plotted to exhibit the effects of the controlling parameters on the dimensionless velocity, temperature, concentration (nanoparticles volume fraction) profiles as well as on the the skin friction factor, rate of heat transfer and rate of mass transfer. The numerical data for the skin friction factor, rate of heat and rate of mass transfer have been provided in tables for various values of the governing parameters. The flow field and other quantities of physical interest were significantly influenced by the controlling parameters. Good agreement was found between the results reported in this thesis and published results from the open literature.